“Dios te diría ‘Yo no te hice esclava’”: percepciones del rol de la mujer en una iglesia cristiana de Lima - Diaz Saenz, Lucia Cristina (2023)
This article analyzes gender perceptions among women in the Agua Viva, Christian church, in Metropolitan Lima and Callao (Peru), based on Francois Dubet’ sociology of experience. The research uses a qualitative approach through interviews with seven members of the Church. The findings show convergences between women’s religious beliefs and their perceptions of gender roles in the family, education, work, and community participation. Although there is consensus among those interviewed about the importance of female participation in public life, there are also tensions between their experiences and views on gender roles in the private sphere, especially around marriage and motherhood. Women justify and interpret their perceptions based, among other elements, on their religious principles, expressing conservative beliefs and others adopting more progressive perspectives. The study highlights the diversity of interpretations and attitudes among participants, challenging the stereotype of extreme conservatism in evangelical churches and revealing nuances in the perspectives of women within these religious communities.